EFEKTIVITAS PELATIHAN KESELAMATAN KERJA DAN PENGGUNAAN ALAT SUNTIK AMAN (SAFETY NEEDLE) TERHADAP PENURUNAN ANGKA NEEDLESTICK INJURY (NSI) PADA PERAWAT NEONATUS: LITERATURE REVIEW - Dewi Mulfiyanti; Andi Satriana; Rismayanti Yamin (Yayasan Nusantara Hasana Berdikari, 2026)
Needlestick Injury (NSI) is a major occupational risk for healthcare workers, potentially leading to the transmission of infectious diseases such as hepatitis B, hepatitis C, and HIV. Neonatal nurses are at high risk due to the frequent use of sharp instruments in clinical procedures. This study aims to analyze the effectiveness of occupational safety training and the use of safe needles in reducing NSI rates. The method used was a literature review with the PRISMA approach. Articles were searched in the PubMed, ScienceDirect, and Google Scholar databases for the years 2014–2024. A total of 15 articles met the inclusion criteria and were analyzed qualitatively. The results showed that occupational safety training increased nurses' knowledge and compliance by 20–45% and reduced the incidence of NSI by 15–35%. The use of safety needles had a more significant impact, with a reduction of 30–60%. The combination of the two interventions resulted in the most optimal reduction of up to 65–80%. Thus, the implementation of continuous occupational safety training and the simultaneous use of safety needles are effective in reducing NSI rates.